A Quranic Perspective on the Nature of Man - Omar Nakib (مجلة الدراسات الاجتماعية, 2005)
Introduction Al-Qur‟ān, preserved in its original form in pure divine language is the last message of Allah (s.w.t) to mankind. Islam, being the last religion and final synthesis of divinely revealed truth, draws in itself all the essential aspects of truth about God and man that were expressed in earlier religions (Austin, 1978). By virtue of being a revelation, Islam aims to establish the leading Muslim Ummah in human life through providing a comprehensive system of thought and action that provides moral guidance in all walks of life. Since al-Qur‟ān lays the foundations of the Islamic way of life, Islam emerges as a comprehensive educational system that aims to build the perfect human personality in such a way to achieve the aims of human existence. So, “any genuine discussion of Islamic education requires sound understanding of its principles” (Abdurrahman, 1982, p.7). Any theory of education must stand on a set of philosophical foundations. For al-Qur‟ān, the philosophical foundations of education, as understood by the present day educators, have not been mentioned explicitly. However, the analysis of al-Qur‟ān and the authentic Sunnah would lead to realize that such philosophical foundations have been systematically treated. Such a treatment could be a basis for the formulation of a comprehensive system of education ever known by mankind. The reason for such an attitude is that Islam, as a final revelation, is particularly detailed in this respect and erects a vast structure of interrelated norms of action and conduct that enable man to saturate his life in unceasing awareness of the divine reality (Algar, 1978) 1.